Perinatal SSRI Exposure Disrupts G Protein-coupled Receptor BAI3 in Developing Dentate Gyrus and Adult Emotional Behavior: Relevance to Psychiatric Disorders. (1st September 2021) - Unroe, Keaton A.; Glover, Matthew E.; Shupe, Elizabeth A.; Feng, Ningping; Clinton, Sarah M.
Highlights: Perinatal exposure to the selective serotonin reuptake inhibitor (SSRI) citalopram increased offspring passive stress coping and anhedonia. Perinatal SSRI exposure increased mRNA expression of G-protein coupled receptor Bai3 and related molecules in the early postnatal dentate gyrus. Transient Bai3 knockdown in perinatal SSRI-exposed dentate gyrus lessened behavioral consequences of perinatal SSRI exposure. Human postmortem work showed BAI3 network dysregulation in limbic brain regions of individuals with depression or schizophrenia. Abstract: Selective serotonin reuptake inhibitor (SSRI) antidepressants are widely prescribed to pregnant women suffering with depression, although the long-term impact of these medications on exposed offspring are poorly understood. Perinatal SSRI exposure alters human offspring's neurodevelopment and increases risk for psychiatric illness in later life. Rodent studies suggest that perinatal SSRI-induced behavioral abnormalities are driven by changes in the serotonin system as well as epigenetic and transcriptomic changes in the developing hippocampus. A major gene altered by perinatal SSRI exposure is the G-protein coupled receptor Brain Angiogenesis Inhibitor 3 (BAI3). Our present study shows that perinatal exposure to the SSRI citalopram increases mRNA expression of Bai3 and related molecules (including its C1ql ligands) in the early postnatal dentate gyrus of male and female offspring. Transient Bai3 mRNA knockdown in perinatal SSRI-exposed dentate gyrus lessened behavioral consequences of perinatal SSRI exposure, leading to increased active stress coping. To determine translational implications of this work, we examined expression of BAI3 and related molecules in hippocampus and prefrontal cortex from patients that suffered with depression or schizophrenia relative to healthy control subjects. We found sex- and region-specific changes in mRNA expression of BAI3 and its ligands C1QL2 and C1QL3 in men and women with a history of psychiatric disorders compared to healthy controls. Together these results suggest that abnormal BAI3 signaling may contribute to molecular mechanisms that drive adverse effects of perinatal SSRI exposure, and show evidence for alterations of BAI3 signaling in the hippocampus of patients that suffer depression and schizophrenia.